ADAMTS5 Deficiency in Calcified Aortic Valves Is Associated With Elevated Pro-Osteogenic Activity in Valvular Interstitial Cells. Issue 7 (July 2017) - Li, Fei; Song, Rui; Ao, Lihua; Reece, T. Brett; Cleveland, Joseph C.; Dong, Nianguo; Fullerton, David A.; Meng, Xianzhong
Abstract : Objective—: Extracellular matrix proteinases are implicated in the pathogenesis of calcific aortic valve disease. The ADAMTS5 (a disintegrin and metalloproteinase with thrombospondin motifs 5) enzyme is secreted, matrix-associated metalloendopeptidase, capable of degrading extracellular matrix proteins, particularly matrilin 2. We sought to determine the role of the ADAMTS5/matrilin 2 axis in mediating the phenotype transition of valvular interstitial cells (VICs) associated with calcific aortic valve disease. Approach and Results—: Levels of ADAMTS5, matrilin 2, and α-SMA (α-smooth muscle actin) were evaluated in calcified and normal human aortic valve tissues and VICs. Calcified aortic valves have reduced levels of ADAMTS5 and higher levels of matrilin 2 and α-SMA. Treatment of normal VICs with soluble matrilin 2 caused an increase in α-SMA level through Toll-like receptors 2 and 4, which was accompanied by upregulation of runt-related transcription factor 2 and alkaline phosphatase. In addition, ADAMTS5 knockdown in normal VICs enhanced the effect of matrilin 2. Matrilin 2 activated nuclear factor (NF) κB and NF of activated T cells complex 1 and induced the interaction of these 2 NFs. Inhibition of either NF-κB or NF of activated T cells complex 1 suppressed matrilin 2's effect on VIC phenotype change. Knockdown of α-SMA reduced and overexpression of α-SMA enhanced the expression of pro-osteogenic factors and calcium deposit formation in human VICs. Conclusions—: Matrilin 2 induces myofibroblastic transition and elevates pro-osteogenic activity in human VICs via activation of NF-κB and NF of activated T cells complex 1. Myofibroblastic transition in human VICs is an important mechanism of elevating the pro-osteogenic activity. Matrilin 2 accumulation associated with relative ADAMTS5 deficiency may contribute to the mechanism underlying calcific aortic valve disease progression. Abstract : Supplemental Digital Content is available in the text.